Composite current collector, pole piece, battery and electric equipment

By setting a safety layer of alternating metal layers and inorganic compound layers in the composite current collector, the safety problem of high-energy-density batteries under mechanical abuse conditions such as needle puncture is solved, and the stability and safety of the battery are improved.

CN120637494APending Publication Date: 2025-09-12GUANGZHOU AUTOMOBILE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510803768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing composite current collectors cannot effectively guarantee the safety of high-energy-density batteries under mechanical abuse conditions such as needle puncture.

Method used

A safety layer of alternating metal layers and inorganic compound layers is set between the base film and the conductive layer to form a multi-layer structure, which increases the Young's modulus of the composite current collector, making it easy to form cracks and break when stretched, thereby achieving local disconnection in the short-circuit area of ​​the battery and separation of the active material from the conductive layer.

Benefits of technology

It effectively controls the short-circuit area, maintains the stability of the battery voltage, ensures personnel safety, and improves the safety of the composite current collector under mechanical abuse conditions such as needle puncture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637494A_ABST
    Figure CN120637494A_ABST
Patent Text Reader

Abstract

According to the composite current collector, the pole piece, the battery and the electric equipment, in the composite current collector, the safety layer is additionally arranged between the base film and the conducting layer, and the safety layer comprises the metal layers and the inorganic compound layers which are alternately arranged in the thickness direction of the composite current collector, so that the Young modulus of the composite current collector is obviously lower than that of a pure metal layer; the composite current collector prepared by the method is high in specific energy and easy to crack and break in a film layer under a tensile condition, can effectively solve the problem that the safety of a high-specific-energy battery under mechanical abuse working conditions such as needling cannot be effectively ensured due to poor safety of an existing composite current collector, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a composite current collector, a pole piece, a battery and an electrical device. Background Art

[0002] The composite current collector is a new type of composite foil material with a "sandwich" structure consisting of a conductive layer and a base film.

[0003] Compared with traditional current collectors, composite current collectors are lightweight and low-cost (low metal content). However, although reports have shown that composite current collectors can improve the safety of battery cells under needle puncture in some ternary / graphite systems, existing composite current collectors still cannot effectively guarantee the safety of high-energy-density batteries (such as 9-series ternary, silicon-doped anode, and lithium metal batteries) under mechanical abuse conditions such as needle puncture.

[0004] Based on this, there is an urgent need to develop a composite current collector to solve the problem that the existing composite current collector cannot effectively cope with mechanical abuse conditions such as acupuncture of high-energy-density batteries. Summary of the Invention

[0005] The embodiments of the present application provide a composite current collector, a pole piece, a battery and an electrical device, aiming to improve the problem that the existing composite current collector has poor safety and cannot effectively ensure the safety of high-energy-density batteries under mechanical abuse conditions such as needle puncture.

[0006] In order to solve the above problems, this application is implemented through the following technical solutions:

[0007] The present application proposes a composite current collector, comprising a base film, a safety layer and a conductive layer stacked together, wherein the safety layer is arranged between the base film and the conductive layer;

[0008] The safety layer includes metal layers and inorganic compound layers alternately arranged along a thickness direction of the composite current collector.

[0009] In the composite current collector provided in the embodiment of the present application, a safety layer is added between the base film and the conductive layer. The safety layer includes a metal layer and an inorganic compound layer alternately arranged along the thickness direction of the composite current collector, so that its Young's modulus is significantly lower than that of the pure metal layer, and it is easy to form cracks and film fractures under tension; therefore, when the battery with the composite current collector undergoes mechanical abuse conditions such as needle puncture, even if the battery temperature does not rise significantly and the polymer layer does not melt or shrink significantly, the safety layer can also form cracks and break, thereby achieving local disconnection in the short-circuit area of ​​the battery and separation of the active material and the conductive layer, which helps to effectively control the short-circuit area, maintain battery voltage stability, and ensure personnel safety. Therefore, the composite current collector proposed in this application can effectively improve the poor safety of existing composite current collectors, which leads to the inability to effectively ensure the safety of high-energy-density batteries under mechanical abuse conditions such as needle puncture, and has good application prospects.

[0010] Furthermore, in the composite current collector, the material of the metal layer includes at least one of copper, zinc, zirconium, titanium, and barium, and the material of the inorganic compound layer includes oxides, sulfides, nitrides, phosphides, or carbides of at least one of copper, zinc, zirconium, titanium, barium, chromium, tungsten, boron, and silicon.

[0011] Furthermore, in the composite current collector, the material of the inorganic compound layer includes at least one of copper oxide, zinc oxide, zirconium oxide, titanium oxide, chromium oxide, cuprous nitride, titanium nitride, boron nitride, silicon nitride, silicon carbide, silicon oxide, titanium carbide, and tungsten carbide.

[0012] Furthermore, the thickness of the metal layer is 10 to 1000 nm, the thickness of the inorganic compound layer is 1 to 50 nm, and the thickness of the safety layer is 50 to 1000 nm.

[0013] Furthermore, the number of the metal layer is 1 to 20 layers, and the number of the inorganic compound layer is 1 to 22 layers.

[0014] Furthermore, the composite current collector further includes a first coating layer, which is disposed between the base film and the safety layer, and is used to increase the bonding force between the base film and the safety layer.

[0015] Furthermore, the material of the first base layer includes at least one of nickel, chromium, titanium, zinc, copper, silicon, or oxides or nitrides thereof.

[0016] Furthermore, the composite current collector further includes a second bottom layer, which is disposed between the conductive layer and the safety layer, and is used to increase the bonding force between the conductive layer and the safety layer.

[0017] Furthermore, the material of the second base layer includes at least one of nickel, chromium, titanium, zinc, copper, silicon, or oxides or nitrides thereof.

[0018] Furthermore, the conductive layer is made of aluminum, aluminum alloy or copper, and / or the thickness of the conductive layer is 0.1-100 μm.

[0019] Furthermore, the material of the base film includes at least one of polyethylene, polyethylene terephthalate, polyimide, polypropylene, polyethylene, polyamide, polyphenylene sulfide, and polyacrylonitrile, and / or the thickness of the base film is 1 to 20 μm.

[0020] The present application also proposes a pole piece comprising the composite current collector as described above.

[0021] The present application also proposes a battery, which includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, and the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer arranged on the negative electrode collector, and at least one of the positive electrode collector and the negative electrode collector adopts the composite current collector as described above.

[0022] Furthermore, when the positive electrode current collector adopts the composite current collector, a first carbon coating layer is further provided between the positive electrode current collector and the positive electrode active material layer;

[0023] In the case where the negative electrode current collector adopts the composite current collector, a second carbon coating layer is further provided between the negative electrode current collector and the negative electrode active material layer.

[0024] The present application also proposes an electrical device, comprising the battery as described above, wherein the battery serves as a power supply for the electrical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the structure of a composite current collector provided in an embodiment of the present application;

[0026] Figure 2 This is a schematic diagram of the structure of the security layer in an embodiment of the present application;

[0027] Figure 3 is a SEM (scanning electron microscope) image of the upper surface of the composite current collector in Example 1 of the present application;

[0028] Figure 4 is a SEM image of the lower surface of the composite current collector in Example 1 of the present application;

[0029] Figure 5 is a cross-sectional SEM image of the composite current collector in Example 1 of the present application;

[0030] Figure 6 is a SEM image of the upper surface of the composite current collector in Example 4 of the present application;

[0031] Figure 7 is a SEM image of the lower surface of the composite current collector in Example 4 of the present application;

[0032] Figure 8 is a cross-sectional SEM image of the composite current collector in Example 4 of the present application;

[0033] Figure 9 is a SEM image of the upper surface of the composite current collector in Example 5 of the present application;

[0034] Figure 10 is a SEM image of the lower surface of the composite current collector in Example 5 of the present application;

[0035] Figure 11 This is a cross-sectional SEM image of the composite current collector in Example 5 of the present application. DETAILED DESCRIPTION

[0036] In order to make the technical problems, technical solutions and beneficial effects solved by this application more clearly understood, this application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.

[0037] Composite current collectors are a new type of composite foil with a "sandwich" structure, consisting of a conductive layer and a base film. Compared with traditional current collectors, composite current collectors are lightweight and low-cost (due to low metal content). However, they suffer from poor safety and cannot effectively guarantee the safety of high-energy-density batteries (such as 9-series ternary, silicon-doped anode, and lithium metal batteries) under mechanical abuse conditions such as needle puncture.

[0038] The applicant found that both academia and industry have reported on the use of composite aluminum current collector products to improve the needle puncture safety of ternary / graphite systems, but there have been no reports on the use of composite copper current collectors to improve battery safety; in addition, the applicant also found that for some highly reactive positive or negative electrode active materials, the simple use of composite aluminum current collector products is not sufficient to improve the safety of the battery cell to a reliable level, and additional optimization is required from the perspective of material or battery cell structure design.

[0039] Based on the above findings, in order to solve the problem that the existing composite current collector is poor in safety and cannot effectively ensure the safety of high-energy-density batteries under mechanical abuse conditions such as needle puncture, the embodiment of the present application provides a composite current collector 100, such as Figure 1 and 2As shown, the composite current collector 100 includes a stacked base film 10, a safety layer 20 and a conductive layer 30, and the safety layer 20 is arranged between the base film 10 and the conductive layer 30, that is, the safety layer 20 is arranged on the surface of the base film 10, and the conductive layer 30 is arranged on the surface of the safety layer 20; the safety layer 20 includes a metal layer 21 and an inorganic compound layer 22 alternately arranged along the thickness direction of the composite current collector.

[0040] In the composite current collector provided in the embodiment of the present application, a safety layer is added between the base film and the conductive layer. The safety layer includes a metal layer and an inorganic compound layer alternately arranged along the thickness direction of the composite current collector, so that its Young's modulus is significantly lower than that of the pure metal layer, and it is easy to form cracks and film fractures under tension; therefore, when the battery with the composite current collector undergoes mechanical abuse conditions such as needle puncture, even if the battery temperature does not rise significantly and the polymer layer does not melt or shrink significantly, the safety layer can also form cracks and break, thereby achieving local disconnection in the short-circuit area of ​​the battery and separation of the active material and the conductive layer, which helps to effectively control the short-circuit area, maintain battery voltage stability, and ensure personnel safety. Therefore, the composite current collector proposed in this application can effectively improve the poor safety of existing composite current collectors, which leads to the inability to effectively ensure the safety of high-energy-density batteries under mechanical abuse conditions such as needle puncture, and has good application prospects.

[0041] Optionally, in one embodiment, the structure of each layer of the composite current collector can be detected by scanning electron microscopy and energy dispersive X-ray spectroscopy (EDS).

[0042] In the composite current collector provided in the embodiment of the present application, a conductive layer may be provided on both sides of the base film, and a safety layer may be provided between the base film and the conductive layer.

[0043] Optionally, in one embodiment, the material of the above-mentioned metal layer includes at least one of copper, zinc, zirconium, titanium, and barium, and the material of the inorganic compound layer includes oxides, sulfides, nitrides, phosphides or carbides of at least one of copper, zinc, zirconium, titanium, barium, chromium, tungsten, boron, and silicon.

[0044] In this embodiment, copper, zinc, zirconium, titanium, barium or other metals or their alloys are used as metal layer materials, and oxides, sulfides, nitrides, phosphides or carbides of at least one of copper, zinc, zirconium, titanium, barium, chromium, tungsten, boron and silicon are used as inorganic compound layer materials. Heterogeneous ductility can be effectively formed between the inorganic compound layer and the metal layer, so that the safety layer is prone to cracks and film rupture under tension.

[0045] In the composite current collector provided in the embodiment of the present application, the metal layer can be prepared by roll-to-roll vacuum evaporation of the metal material.

[0046] In the composite current collector provided in the embodiment of the present application, a specific atmosphere such as nitrogen (N2), oxygen (O2), methane (CH 4) , hydrogen (H2), argon (Ar), acetylene (C2H2), hydrogen fluoride (HF), hydrogen sulfide (H2S), ammonia (NH3), carbon dioxide (CO2), boron trichloride (BCl3), hexafluoroethane (C2F6) and other gases, and vacuum evaporation, magnetron sputtering or chemical alloy plating methods are used for coating to obtain an inorganic compound layer; inorganic compounds such as metal carbides, metal phosphides, etc. can also be directly evaporated or magnetron sputtered.

[0047] Optionally, in one embodiment, the material of the inorganic compound layer specifically includes at least one of copper oxide, zinc oxide, zirconium oxide, titanium oxide, chromium oxide, cuprous nitride, titanium nitride, boron nitride, silicon nitride, silicon carbide, silicon oxide, titanium carbide, tungsten carbide and the like, which can provide a layer of inorganic compound layer with a very "brittle" texture, and then form a multi-layer structure safety layer protection mechanism with the metal layer.

[0048] In the composite current collector provided in the embodiment of the present application, the thickness of the safety layer is the sum of the thickness of the metal layer and the thickness of the inorganic compound. When there are multiple layers of metal layers and inorganic compound layers, the thickness of the safety layer is the sum of the thickness of the multiple metal layers and the thickness of the multiple inorganic compounds.

[0049] Optionally, in one embodiment, the thickness of the metal layer is 10 to 1000 nm, the thickness of the inorganic compound layer is 1 to 50 nm, and the thickness of the security layer is 50 to 1000 nm.

[0050] In this embodiment, the thickness of the metal layer is set to 10 to 1000 nm, the thickness of the inorganic compound layer is set to 1 to 50 nm, and the thickness of the safety layer is 50 to 1000 nm. This is convenient for coating by magnetron sputtering or chemical alloy plating, and can also effectively ensure the heterogeneous ductility between the metal layer and the inorganic compound layer.

[0051] The composite current collector provided in the embodiments of the present application can be used as either a positive electrode current collector or a negative electrode current collector.

[0052] Optionally, when the composite current collector is used as the positive electrode current collector, the metal layer can be made of copper, while the inorganic compound layer can be made of copper oxide. Copper is a dense, highly ductile, purple-red metal with excellent electrical conductivity (second only to silver), outstanding thermal conductivity, and a high melting point (1083°C), effectively balancing electrical conductivity and cost-effectiveness.

[0053] Optionally, when the composite current collector is used as the negative electrode current collector, the metal layer can be made of aluminum, and the inorganic compound layer can be made of aluminum oxide (Al2O3). Aluminum is a light, soft, silvery-white metal with good electrical and thermal conductivity and a low melting point, making it an excellent conductive material for the current collector.

[0054] Optionally, in the composite current collector provided in the embodiment of the present application, the metal layer and the inorganic compound layer are alternately arranged between the base and the conductive layer along the thickness direction of the composite current collector. The metal layer and the inorganic compound layer may be adjacent to the first surface and / or the second surface of the base film, respectively, that is, the metal layer may be in contact with the base film, and the inorganic compound layer may be in contact with the conductive layer; or the metal layer may be in contact with the conductive layer, and the inorganic compound layer may be in contact with the base film. The thickness of each metal layer may be consistent or inconsistent; the thickness of each compound layer may be consistent or inconsistent. The number of layers and thickness ratio of the metal layer and the inorganic compound layer are related to the negative electrode material, the negative electrode compaction density, the positive electrode side compaction, whether a composite current collector is used on the positive electrode side, the battery cell capacity and the battery cell structure.

[0055] For example, when the compaction density of the battery cell is high (that is, the energy density of the battery cell is high), the thickness and number of the safety layer need to be increased accordingly; when the compaction density of the battery cell is low (that is, the energy density of the battery cell is low), the thickness and number of the safety layer need to be reduced accordingly; when the positive electrode current collector adopts a composite current collector, or even a high-safety composite current collector, the safety layer may not be used in the negative electrode current collector, or a thinner safety layer may be used; when the negative electrode current collector adopts a composite current collector, or even a high-safety composite current collector, the safety layer may not be used in the positive electrode current collector, or a thinner safety layer may be used.

[0056] Optionally, the thickness of the metal layer may be in a range of one or any two of 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, and 1000 nm.

[0057] Alternatively, the thickness of the inorganic compound layer may be within the range of one or any two of 1 nm, 2 nm, 5 nm, 10 nm, 20 nm, and 50 nm.

[0058] Optionally, the thickness of the security layer may be within a range of one or any two of 50 nm, 100 nm, 200 nm, 500 nm, and 1000 nm.

[0059] Optionally, in one embodiment, the number of metal layers is 1 to 20 layers, and the number of inorganic compound layers is 1 to 22 layers, which can not only meet the heterogeneous ductility between the metal layer and the inorganic compound layer, so that the safety layer is prone to cracking and film rupture under tension, but also match the negative electrode material, negative electrode compaction density, positive electrode side compaction density, battery cell capacity and battery cell structure to achieve a balance between energy density, safety and economy.

[0060] Optionally, the number of metal layers can be set to a range of one or any two of 1 layer, 2 layers, 5 layers, 10 layers, 15 layers, and 20 layers.

[0061] Alternatively, the number of the inorganic compound layer may be set to a range of one or any two of 1, 2, 5, 10, 15, 20, and 22 layers.

[0062] Optionally, in one embodiment, the composite current collector 100 further includes a first coating layer 40, which is disposed between the base film 10 and the safety layer 20. The metal layer 21 and the inorganic compound layer 22 are sequentially stacked between the first coating layer 40 and the conductive layer 30, and may be adjacent to the first surface and / or the second surface of the first coating layer 40, respectively. That is, the metal layer 21 may be in contact with the first coating layer 40, while the inorganic compound layer 22 may be in contact with the conductive layer 30; or the metal layer 21 may be in contact with the conductive layer 30, while the inorganic compound layer 22 may be in contact with the first coating layer 40. The first coating layer 40 is used to increase the bonding force between the base film 10 and the safety layer 20.

[0063] In this embodiment, a conductive layer 30 may be provided on both sides of the base film 10, and a safety layer 20 may be provided between the base film 10 and the conductive layer 30. Then, the first primer layer 40 may be provided between the base film 10 and the safety layers 20 on both sides.

[0064] In this embodiment, by disposing the first primer layer 40 between the base film 10 and the security layer 20 , the bonding force between the base film 10 and the security layer 20 can be increased.

[0065] Optionally, in a specific embodiment, the material of the first primer layer includes at least one of nickel, chromium, titanium, zinc, copper, silicon, or oxides or nitrides thereof, which can effectively increase the bonding force between the base film and the security layer.

[0066] Optionally, in one embodiment, the composite current collector 100 further includes a second coating layer 50 , which is disposed between the conductive layer 30 and the safety layer 20 . The second coating layer 50 is used to increase the bonding force between the conductive layer 30 and the safety layer 20 .

[0067] In this embodiment, a conductive layer 30 may be provided on both sides of the base film 10, and a safety layer 20 may be provided between the base film 10 and the conductive layer 30. Then, the second base layer 50 may be provided between the safety layer 20 and the conductive layer 30 on both sides.

[0068] In this embodiment, the metal layer 21 and the inorganic compound layer 22 are alternately arranged between the first bottom layer 40 and the second bottom layer 50 along the thickness direction of the composite current collector, and can be adjacent to the surface of the second bottom layer 50 or the first bottom layer 10, respectively, that is, the metal layer 21 can be in contact with the first surface of the second bottom layer 50, the conductive layer 30 can be in contact with the second surface of the second bottom layer 50, and the inorganic compound layer 22 can be in contact with the first surface of the first bottom layer 40, and the second surface of the first bottom layer 40 can be in contact with the base film 10; or the inorganic compound layer 22 can be in contact with the first surface of the second bottom layer 50, the conductive layer 30 can be in contact with the second surface of the second bottom layer 50, and the metal layer 21 can be in contact with the first surface of the first bottom layer 40, and the second surface of the first bottom layer 40 can be in contact with the base film 10.

[0069] In this embodiment, by disposing the second primer layer 50 between the conductive layer 30 and the safety layer 20 , the bonding force between the conductive layer 30 and the safety layer 20 can be increased.

[0070] Optionally, in a specific embodiment, the material of the second primer layer includes at least one of nickel, chromium, titanium, zinc, copper, silicon, or oxides or nitrides thereof, which can effectively increase the bonding force between the conductive layer and the safety layer.

[0071] In the composite current collector provided in the embodiment of the present application, the conductive layer can be aluminum, aluminum alloy or copper, and the thickness of the conductive layer can be 0.1 to 100 μm, which is convenient for preparation using physical vapor deposition PVD, chemical vapor deposition CVD, water electroplating and other methods, and can also effectively improve the overall conductive performance of the composite current collector.

[0072] Optionally, the thickness of the conductive layer may be within a range of one or any two of 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, and 100 μm.

[0073] In the composite current collector provided in the embodiment of the present application, the material of the above-mentioned base film includes at least one of polyethylene, polyethylene terephthalate, polyimide, polypropylene, polyethylene, polyamide, polyphenylene sulfide, and polyacrylonitrile. The thickness of the base film can be 1 to 20 μm, which can effectively take into account safety, battery energy density and processing economy.

[0074] Optionally, the thickness of the base film may be within the range of one or any two of 1 μm, 2 μm, 5 μm, 10 μm, 15 μm, and 20 μm.

[0075] An embodiment of the present application also provides a pole piece, comprising the composite current collector as described above.

[0076] The electrode piece can be a positive electrode piece or a negative electrode piece.

[0077] An embodiment of the present application also provides a battery, which includes a positive electrode plate and a negative electrode plate; the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, and the negative electrode plate includes a negative electrode collector and a negative electrode active material layer arranged on the negative electrode collector, and at least one of the positive electrode collector and the negative electrode collector adopts the composite current collector as described above.

[0078] Because at least one of the positive current collector and the negative current collector adopts the composite current collector as mentioned above, and the composite current collector adds a safety layer between the base film and the conductive layer, the safety layer includes a metal layer and an inorganic compound layer alternately arranged along the thickness direction of the composite current collector, so that its Young's modulus is significantly lower than that of the pure metal layer, and it is easy to form cracks and the film layer breaks under tension; therefore, when the battery with the composite current collector undergoes mechanical abuse conditions such as needle puncture, even if the battery temperature does not rise significantly and the polymer layer does not melt or shrink significantly, the safety layer can also form cracks and break, thereby achieving local disconnection in the short-circuit area of ​​the battery and separation of the active material and the conductive layer, which helps to effectively control the short-circuit area, maintain battery voltage stability, and ensure personnel safety.

[0079] In the battery provided in the embodiment of the present application, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material can be selected from lithium nickel cobalt manganese oxide (N x M y C z ,x+y+z=1), lithium iron manganese phosphate (LiFexMnyPO4,x+y=1), lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium-rich manganese base, lithium nickel manganese oxide (LMNO), lithium vanadium phosphate (Li3V2(PO4)3, LiVOPO4) and other common positive electrode active materials are arranged on the double-side surfaces of the above-mentioned composite current collector for the positive electrode, and the thickness range can be 10 to 150um.

[0080] In the battery provided in the embodiment of the present application, the positive electrode active material layer also includes a conductive agent and a binder; optionally, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene, and the binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.

[0081] In some embodiments, the positive electrode sheet is prepared as follows: the components for preparing the positive electrode sheet, such as the positive electrode material, the adhesive and any other components, are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on both sides of a positive electrode current collector such as aluminum foil; and after baking, rolling, cutting, striping and other processes, the positive electrode sheet can be obtained.

[0082] When the positive electrode current collector adopts a composite current collector, the negative electrode current collector may be a metal current collector or a composite current collector; when the negative electrode current collector adopts a composite current collector, the positive electrode current collector may be a metal current collector or a composite current collector.

[0083] Optionally, in one embodiment, when a composite current collector is used as the positive electrode current collector, a first carbon coating layer is further provided between the positive electrode current collector and the positive electrode active material layer, which can effectively reduce the interface resistance, inhibit the oxidation of the aluminum foil, and improve the bonding strength.

[0084] In some embodiments, the carbon coating layer includes a conductive agent (acetylene black, graphene, carbon nanotubes (CNTs) or a composite conductive agent (such as a graphene-CNT hybrid system)), a binder (acrylic polymer (such as butyl acrylate), polyurethane (PU) or a photocurable resin (such as polyethylene glycol diacrylate)), a solvent (deionized water, N-methylpyrrolidone (NMP) or ethanol (selected according to the slurry system)) and an additive (dispersant (PVP), a wetting agent (Triton X-100) or an antioxidant (BHT)).

[0085] The first carbon coating layer is arranged on both sides of the composite current collector for the positive electrode away from the base film, with a single-side carbon coating thickness of 0.5 to 4.0 μm, and is prepared by gravure coating or micro-concave coating.

[0086] Optionally, in one embodiment, when the negative electrode current collector adopts a composite current collector, a second carbon coating layer is further provided between the negative electrode current collector and the negative electrode active material layer, which can effectively inhibit lithium dendrites, enhance mechanical strength, and alleviate volume expansion.

[0087] In some embodiments, the second carbon-coated layer comprises: a conductive agent (acetylene black, carbon nanotubes (CNT), graphene or composite carbon materials (such as CNT-graphene hybrid systems)), a binder (polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) or carboxymethyl cellulose (CMC)), a solvent (deionized water, NMP or acetone (selected according to the solubility of the binder)), an additive (conductive carbon black (Super P), an anti-swelling agent (such as a polydopamine coating)).

[0088] The second carbon-coated layer is disposed on the bilateral surfaces of the above-mentioned composite current collector for the negative electrode away from the base film, and the carbon coating thickness is 0.5-2.0 μm on a single side, and is prepared by gravure coating or microgravure coating, extrusion coating.

[0089] In the battery provided by the embodiment of the present application, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material can be selected from at least one of carbon-based materials, silicon-based materials, alloy materials, titanium-based materials, and composite systems.

[0090] Among them, the carbon-based materials include graphite-based, hard carbon / soft carbon; the graphite-based includes natural graphite (C), artificial graphite, mesocarbon microbeads (MCMB), etc.; the hard carbon / soft carbon includes disordered carbon materials (such as hard carbon Li x C6, soft carbon Li y C6, etc., which are suitable for fast charging scenarios.

[0091] Among them, the silicon-based materials include elemental silicon (Si), silicon monoxide (SiO x , 0.8 < x < 1.6), silicon-carbon composite materials (Si / C, SiO x / C), etc.; the silicon-carbon composite materials inhibit volume expansion through carbon coating, and the silicon content is controlled at 5-30 wt%.

[0092] Among them, the alloy materials include lithium metal (Li), lithium alloys (Li-M, M = Sn, Al, Mg, Zn, Ag, etc., and the mass ratio of Li is 10-99.5%), tin-based materials (Sn, SnO2), antimony-based materials (Sb2O3), etc.;

[0093] Among them, the titanium-based materials include lithium titanate (Li4Ti5O 12 , LTO), etc., which are zero-strain materials and are used for long-life batteries;

[0094] Among them, the composite systems include: graphite / silicon gradient composite layers (such as surface layer Si / C + bottom layer graphite), prelithiated materials (Li x Si, Li y C); sulfide / carbon composites (such as MoS2 / C, WS2 / C), which have both high capacity and stability;

[0095] The negative electrode active material layer is arranged on both sides of the negative electrode composite current collector, and has a thickness of 0 to 100 μm.

[0096] Among them, the lithium alloy Li-M can be an alloy formed by metallic lithium and one or more substances selected from the group consisting of gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus, and bismuth, with a mass content of metallic lithium of 0.5 to 99.5%.

[0097] The negative electrode active material layer can be prepared by roll pressing, physical vapor deposition (PVD), wet coating, dry electrode and other methods.

[0098] When the negative electrode active material layer is made of a lithium-containing material, its surface may have a lithium alloy Li-M layer or an artificial SEI layer.

[0099] When the negative electrode active material layer does not contain lithium, its surface may have a lithium supplement layer made of lithium metal, lithium alloy Li-M or lithium-containing compound, and the thickness may be 2 to 20 μm.

[0100] In some embodiments, the negative electrode plate is a metal lithium plate.

[0101] In other embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The above-mentioned negative electrode active material layer can adopt negative electrode active materials used for batteries, and the negative electrode active materials include any one of hard carbon, soft carbon, graphite, and silicon oxide, or a combination of at least two of them.

[0102] In the case where the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode sheet is prepared as follows: the components for preparing the negative electrode sheet, such as the negative electrode active material, the binder, and the conductive agent, are dispersed in a solvent such as deionized water to form a negative electrode slurry; the negative electrode slurry is coated on both sides of a negative electrode current collector such as copper foil; and after processes such as baking, rolling, cutting, and slitting, the negative electrode sheet can be obtained.

[0103] The battery provided by the embodiment of the present invention further includes a separator and an electrolyte.

[0104] The diaphragm can be selected from materials such as polypropylene PP, polyethylene PE and composite films thereof.

[0105] The electrolyte acts as an ion conductor between the positive and negative electrodes. The electrolyte can be liquid, gel, or fully solid. In some embodiments, the electrolyte can be selected from inorganic solid electrolytes (halide solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes), polymer solid electrolytes, and composite solid electrolytes (inorganic filler + polymer matrix). In some embodiments, the electrolyte is a liquid electrolyte, which includes an electrolyte salt and a solvent. The electrolyte salt is a lithium salt, and the solvent includes a cyclic ester solvent and a chain ester solvent. In some embodiments, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, and γ-butyrolactone; the chain ester solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, and diphenyl carbonate. In some embodiments, the organic solvent includes fluoroethylene carbonate, ethylene carbonate, propylene carbonate, and ethyl methyl carbonate.

[0106] In actual applications, the negative electrode sheet, the separator and the positive electrode sheet are stacked in order and wound to obtain a core, the core is packaged to obtain a bare cell, and the bare cell is baked and then injected, formed, sealed and sorted to obtain the above-mentioned battery.

[0107] In some embodiments, a liquid laminate battery, a liquid wound battery, or a liquid cylindrical battery can be formed by a negative electrode sheet, a positive electrode sheet, a separator, and an electrolyte.

[0108] In some embodiments, a negative electrode sheet, a positive electrode sheet, and a gel electrolyte may be used to form a semi-solid laminated battery, a semi-solid wound battery, or a semi-solid cylindrical battery.

[0109] In some embodiments, a negative electrode sheet and a positive electrode sheet, a solid electrolyte and 0.5-50% electrolyte additives can be respectively formed into a semi-solid laminated battery, a semi-solid wound battery or a semi-solid cylindrical battery;

[0110] In some embodiments, the negative electrode sheet, the positive electrode sheet, and the solid electrolyte can be used to form a solid-state laminated battery, a solid-state wound battery, or a solid-state cylindrical battery.

[0111] The present invention also provides an electrical device, which includes the above-mentioned battery, and the battery serves as a power supply for the electrical device.

[0112] For the above-mentioned electrical equipment embodiment, it includes the above-mentioned battery and can achieve the same technical effect. In order to avoid repetition, it will not be described here. For relevant matters, please refer to the partial description of the battery embodiment.

[0113] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention is further described below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0114] The present invention is described in detail below by way of examples.

[0115] Test method:

[0116] (1) Needle penetration test: Use a high-temperature resistant steel needle with a diameter of 3 / 5 / 8 mm (the cone angle of the needle tip is 45-60 degrees, and the surface of the needle is smooth, free of rust, oxide layer and oil stains) to penetrate the battery cell plate at a speed of 1 mm / s from a direction perpendicular to the battery cell plate. The penetration position should be close to the geometric center of the needle hole in the splint. The steel needle stays in the battery cell and is observed for 1 hour. Monitor the battery voltage and temperature changes. If the battery does not catch fire or explode within 1 hour, it is considered to have passed. Otherwise, it is considered to have failed.

[0117] Example 1

[0118] (1) Preparation of positive electrode current collector

[0119] Using 4.5μm thick PP as the base film, a metal layer is prepared on both sides of the base film by magnetron sputtering priming and water electroplating thickening. Subsequently, an inorganic compound layer naturally forms in the atmosphere to form a safety layer. The metal layer is made of copper with a single layer thickness of 500nm; the inorganic compound layer is made of copper oxide (CuO) with a single layer thickness of 2nm.

[0120] The second bottom layer is prepared on the surface of the device away from the base film on both sides of the safety layer by magnetron sputtering. The second bottom layer is made of titanium and has a thickness of 50nm.

[0121] A conductive layer was prepared on the surface of the second bottom layer on both sides away from the base film by vacuum evaporation. The conductive layer was made of aluminum and had a total thickness of 0.4 μm to obtain a composite current collector as the positive electrode current collector.

[0122] (2) Preparation of positive electrode sheet

[0123] The above-mentioned positive electrode materials high nickel ternary NCM811, conductive carbon black, single-walled carbon nanotubes, fast ion conductor suspension, and PVDF are mixed evenly in a mass ratio of 95.5:1:0.5:1:2, and NMP solvent is added and stirred under vacuum conditions to mix evenly. The above slurry is coated on both sides of 14um carbon-coated aluminum foil and placed in an oven at a high temperature of 110°C for drying. Subsequently, the positive electrode plate is prepared through processes such as rolling, cutting, and slitting. Among them, the size of the positive electrode plate area is 118*408mm, the size of the tab area is 40*25mm, the short side of the plate is connected to the short side of the tab, and the surface capacity is 4mAh / cm 2 .

[0124] (3) Preparation of negative electrode sheet

[0125] A 4.5 μm thick PP film was used as the base film. A 1 μm thick pure copper film was deposited on both sides of the base film using a magnetron primer seed layer + water electroplating method to prepare the negative electrode current collector.

[0126] The negative electrode active material, metallic lithium, is prepared on both sides of the negative electrode current collector by vacuum evaporation, with a purity of more than 99.99% and a thickness of 20 μm;

[0127] Cut the interactive two-stage negative electrode sheet, the negative electrode area size is 120*410mm, the tab area size is 40*25mm, and the short side of the electrode sheet is connected to the short side of the tab.

[0128] (4) Preparation of diaphragm

[0129] Celgard 2400 polypropylene film was selected as the diaphragm.

[0130] (5) Preparation of electrolyte

[0131] The main solvent is dimethyl ether (DME) with a content of 53% wt, and the diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) with a content of 35% wt. After mixing, an organic solvent is obtained, and then lithium salt lithium bistrifluoromethanesulfonyl imide (LiTFSI) is dissolved in the above organic solvent at a mass fraction of 12% wt to prepare an electrolyte.

[0132] (6) Preparation of batteries

[0133] The above-mentioned positive electrode sheets, negative electrode sheets, separators, electrolytes, and aluminum-plastic films are assembled into a soft-pack laminated battery including 15 positive electrode sheets and 6 negative electrode sheets; wherein the liquid injection amount is 2g / Ah and the thickness of the aluminum-plastic film is 113μm.

[0134] Example 2

[0135] The difference between Example 2 and Example 1 is that in step (1), the material of the second base layer is adjusted to Ni.

[0136] Example 3

[0137] The difference between Example 3 and Example 1 is that, in step (1), a PET with a thickness of 6 μm is used as a base film, and a pure aluminum with a thickness of 1 μm is prepared on both sides of the base film by a one-time plating method to prepare a positive electrode current collector;

[0138] In step (3), a PET film with a thickness of 6 μm was used as a base film, and a first base layer made of Al2O3 and a thickness of 50 nm was prepared on both sides of the base film by oxygen evaporation.

[0139] A metal layer and an inorganic compound layer are formed on the surfaces of the first primer layer on both sides in an alternating order of metal layer, inorganic compound layer, and metal layer to form a 500nm thick safety layer. The metal layer is formed by vacuum evaporation of aluminum, and the inorganic compound layer is formed by vacuum evaporation of aluminum with oxygen introduced. The metal layer is made of aluminum with a single layer thickness of 45nm, and the inorganic compound layer is made of aluminum oxide (Al2O3) with a single layer thickness of 5nm.

[0140] A second bottom layer is prepared on the surface of the device away from the base film on both sides of the safety layer by magnetron sputtering. The second bottom layer is made of titanium and has a thickness of 50nm.

[0141] A conductive layer was prepared on the surface of the second bottom layer on both sides away from the base film by vacuum evaporation. The conductive layer was made of copper and had a total thickness of 0.4 μm to obtain a composite current collector as the negative electrode current collector.

[0142] Example 4

[0143] The difference between Example 4 and Example 3 is that in step (3), the thickness of the security layer is adjusted to 1000 nm.

[0144] Example 5

[0145] The difference between Example 5 and Example 3 is that in step (3), the material of the second base layer is adjusted to Ni.

[0146] Example 6

[0147] The difference between Example 6 and Example 3 is that in step (3), the thickness of the security layer is adjusted to 1000 nm, the thickness of the metal layer is adjusted to 80 nm, and the thickness of the inorganic compound layer is adjusted to 20 nm.

[0148] Example 7

[0149] The difference between Example 7 and Example 3 is that in step (3), the material of the metal layer is adjusted to aluminum, the material of the inorganic compound layer is adjusted to aluminum nitride (AlN), and the inorganic compound layer is prepared by vacuum evaporating aluminum by introducing nitrogen.

[0150] Example 8

[0151] The difference between Example 8 and Example 1 is that in step (3), the negative electrode current collector is the same as that in Example 4.

[0152] Example 9

[0153] The difference between Example 9 and Example 1 is that in step (3), the negative electrode current collector is the same as that in Example 5.

[0154] Comparative Example 1

[0155] The difference between Comparative Example 1 and Example 3 is that in step (3), PP with a thickness of 4.5 μm is used as the base film; a first base layer is prepared on both sides of the base film by magnetron sputtering, and the material is Ti with a thickness of 10 nm; a conductive layer is prepared on the surface of the first base layer on both sides away from the base film by first magnetron priming with a 10 nm seed layer and then water electroplating, and the conductive layer is made of copper with a total thickness of 1 μm, to obtain a composite current collector as the negative electrode current collector.

[0156] Comparative Example 2

[0157] The difference between Comparative Example 2 and Example 3 is that, in step (3), the base film is adjusted to a thickness of 4.5 μm PP; a first base layer is prepared on both sides of the base film by magnetron sputtering, the material is Ti, and the thickness is 10 nm; the safety layer is adjusted to a pure aluminum layer with a thickness of 1000 nm; a conductive layer is prepared on the surface of the second base layer on both sides away from the base film by first magnetron coating a 10 nm seed layer and then water electroplating, the conductive layer is made of copper and has a total thickness of 1 μm, and a composite current collector is obtained as a negative electrode current collector.

[0158] The upper surface, lower surface and cross section of the composite current collector in Example 1 were subjected to scanning electron microscopy and EDS element analysis, and the scanning electron microscopy test results were as follows: Figures 3-5 As shown, the EDS element analysis results are shown in Tables 1 to 3 respectively. It can be seen that the main metal elements constituting the current collector are aluminum and copper, and the base material is titanium.

[0159] Table 1

[0160]

[0161] Table 2

[0162]

[0163]

[0164] Table 3

[0165]

[0166] The upper surface, lower surface and cross section of the composite current collector in Example 4 were subjected to scanning electron microscopy and EDS element analysis, and the scanning electron microscopy test results were as follows: Figures 6-8 As shown, the EDS element analysis results are shown in Tables 4 to 6 respectively. It can be seen that the main metal elements of the current collector are aluminum and copper, and the base material is titanium.

[0167] Table 4

[0168]

[0169] Table 5

[0170]

[0171]

[0172] Table 6

[0173]

[0174] The upper surface, lower surface and cross section of the composite current collector in Example 5 were subjected to scanning electron microscopy and EDS element analysis, and the scanning electron microscopy test results were as follows: Figures 9-11 As shown, the EDS element analysis results are shown in Tables 7 to 9 respectively. It can be seen that the main metal elements constituting the current collector are aluminum and copper, and the base material is nickel.

[0175] Table 7

[0176]

[0177] Table 8

[0178]

[0179]

[0180] Table 9

[0181]

[0182] The batteries prepared in each embodiment and comparative example were subjected to needle penetration test, and the results are shown in Table 10.

[0183] Table 10

[0184]

[0185]

[0186] As can be seen from Table 10, the composite current collector provided in the embodiment of the present application effectively reduces the Young's modulus of the safety layer by introducing a safety layer between the metal layer and the inorganic compound layer, making the safety layer more prone to cracks and fractures when stretched, and therefore has a good pass rate for needle penetration tests of different specifications.

[0187] In summary, in the composite current collector provided in the embodiment of the present application, a safety layer is added between the base film and the conductive layer. The safety layer includes a metal layer and an inorganic compound layer alternately arranged along the thickness direction of the composite current collector, so that its Young's modulus is significantly lower than that of the pure metal layer, and it is easy to form cracks and film fractures under tension; therefore, when the battery with the composite current collector undergoes mechanical abuse conditions such as needle puncture, even if the battery temperature does not rise significantly and the polymer layer does not melt or shrink significantly, the safety layer can also form cracks and break, thereby achieving local disconnection in the short-circuit area of ​​the battery and separation of the active material and the conductive layer, which helps to effectively control the short-circuit area, maintain battery voltage stability, and ensure personnel safety. Therefore, the composite current collector proposed in this application can effectively improve the poor safety of existing composite current collectors, which leads to the inability to effectively guarantee the safety of high-energy-density batteries under mechanical abuse conditions such as needle puncture, and has good application prospects.

[0188] Terminology

[0189] In this application, a plurality refers to two or more.

[0190] The terms "first," "second," "third," "fourth," etc. (if any) in this application are used to distinguish similar objects and are not necessarily used to describe a particular sequential order.

[0191] The term "and / or" in this application simply describes an association between related objects, indicating that three possible relationships exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this application generally indicates that the related objects are in an "or" relationship.

[0192] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, a statement that the method includes steps A and B indicates that the method may include steps A and B performed sequentially, or steps B and A performed sequentially. For example, a statement that the method may also include step C indicates that step C may be added to the method in any order, for example, the method may include steps A, B, and C, or steps A, C, and B, or steps C, A, and B, etc.

[0193] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A composite current collector, characterized in that: The invention comprises a base film, a safety layer and a conductive layer which are stacked together, wherein the safety layer is arranged between the base film and the conductive layer; The safety layer includes metal layers and inorganic compound layers alternately arranged along a thickness direction of the composite current collector.

2. The composite current collector according to claim 1, characterized in that The material of the metal layer includes at least one of copper, zinc, zirconium, titanium, and barium, and the material of the inorganic compound layer includes oxide, sulfide, nitride, phosphide or carbide of at least one of copper, zinc, zirconium, titanium, barium, chromium, tungsten, boron, and silicon.

3. The composite current collector according to claim 1, wherein: The material of the inorganic compound layer includes at least one of copper oxide, zinc oxide, zirconium oxide, titanium oxide, chromium oxide, cuprous nitride, titanium nitride, boron nitride, silicon nitride, silicon carbide, silicon oxide, titanium carbide, and tungsten carbide.

4. The composite current collector according to claim 1, characterized in that The thickness of the metal layer is 10 to 1000 nm, the thickness of the inorganic compound layer is 1 to 50 nm, and the thickness of the safety layer is 50 to 1000 nm.

5. The composite current collector according to claim 4, characterized in that: The number of the metal layer is 1 to 20, and the number of the inorganic compound layer is 1 to 22.

6. The composite current collector according to claim 1, characterized in that The composite current collector further includes a first coating layer, which is disposed between the base film and the safety layer, and is used to increase the bonding force between the base film and the safety layer.

7. The composite current collector according to claim 6, characterized in that: The material of the first underlying layer includes at least one of nickel, chromium, titanium, zinc, copper, silicon, or oxides or nitrides thereof.

8. The composite current collector according to claim 1, characterized in that: The composite current collector further includes a second bottom layer, which is disposed between the conductive layer and the safety layer, and is used to increase the bonding force between the conductive layer and the safety layer.

9. The composite current collector according to claim 8, characterized in that: The material of the second primer layer includes at least one of nickel, chromium, titanium, zinc, copper, silicon, or oxides or nitrides thereof.

10. The composite current collector according to any one of claims 1 to 9, characterized in that: The conductive layer is made of aluminum, aluminum alloy or copper, and has a thickness of 0.1 to 100 μm.

11. The composite current collector according to any one of claims 1 to 9, characterized in that: The material of the base film includes at least one of polyethylene, polyethylene terephthalate, polyimide, polypropylene, polyethylene, polyamide, polyphenylene sulfide, and polyacrylonitrile, and / or the thickness of the base film is 1 to 20 μm.

12. A pole piece, characterized in that: The composite current collector comprises the composite current collector according to any one of claims 1 to 11.

13. A battery, characterized in that: The battery includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, and the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer arranged on the negative electrode collector, and at least one of the positive electrode collector and the negative electrode collector adopts the composite current collector according to any one of claims 1 to 11.

14. The battery according to claim 13, characterized in that In the case where the positive electrode current collector adopts the composite current collector, a first carbon coating layer is further provided between the positive electrode current collector and the positive electrode active material layer; In the case where the negative electrode current collector adopts the composite current collector, a second carbon coating layer is further provided between the negative electrode current collector and the negative electrode active material layer.

15. An electrical device, characterized in that: The device comprises a battery as described in claim 13 or 14, wherein the battery serves as a power supply for the electrical device.